2015
DOI: 10.1021/acsmacrolett.5b00045
|View full text |Cite
|
Sign up to set email alerts
|

“Brill Transition” Shown by Green Material Poly(octamethylene carbonate)

Abstract: Poly­(octamethylene carbonate) (POMC), as the eighth member of the newly developed biodegradable aliphatic polycarbonate family, demonstrates a reversible crystal–crystal transition, which is highly similar to Brill transition extensively studied in the nylon family. With the dipole–dipole interaction in POMC much weaker than the hydrogen bonding, POMC exhibits its “Brill transition” temperature at around 42 °C, much lower than nylons. The two crystalline structures of POMC at below and above the transition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 35 publications
16
48
0
Order By: Relevance
“…For PC8, there is an α to β (Brill-like transition as reported in the literature) transition at ∼33 °C followed by the melting of the β crystals at ∼58 °C. These transitions are in line with those reported by Zhao et al in PC8 and by us in a preceding work …”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…For PC8, there is an α to β (Brill-like transition as reported in the literature) transition at ∼33 °C followed by the melting of the β crystals at ∼58 °C. These transitions are in line with those reported by Zhao et al in PC8 and by us in a preceding work …”
Section: Resultssupporting
confidence: 56%
“…The Brill-like transition was attributed to the reversible transition from trans-dominated conformations (in the α phase (at low temperatures)) to the coexistence of trans/gauche conformations (in the β phase (at high temperature)) of methylene sequences. Additionally, a weakening of the dipole–dipole interaction of the carbonyl groups was also observed . These results were recently corroborated in PC8 by Pérez-Camargo et al Similar but even clearer changes were found in PC6-D at higher temperatures due to the dithiocarbonate groups .…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations